AB1169 Polymorphisms of D6S273 microsatellite: Potential basis for differentiating HLA-B27/B7 positive patients with polyarticular course of JIA from juvenile spondyloarthritis patients?. (23rd January 2014) - Lamot, L.; Vidovic, M.; Grubic, Z.; Tambic Bukovac, L.; Harjacek, M.
Abstract : Background: Juvenile idiopathic arthritis (JIA) is a heterogeneous disease and the distinction among various subtypes under ILAR criteria is often unclear. Very few clinical and laboratory findings can help in predicting the course and severity of the disease in the individual patient. A recent publication suggests that HLA-B27 positive JIA patients have more extended disease [1], compared to juvenile spondyloarthritis HLA-B27 positive patients. To our knowledge, there is no reliable, clinical or laboratory marker that can differentiate these two groups of HLA-B27 positive patients. Objectives: The aim of the present pilot study was to investigate polymorphisms of the D6S273 microsatellite located in the last 8 introns of the LY6G6D gene within the MHC class III region. There are 27 members of this LY6G6D gene family described so far in the human genome that have definite or putative immune related roles. We have shown previously that HLA-B*27/HLA-B*07 in combination with the D6S273-134 allele is associated with an increased susceptibility to juvenile spondyloarthritis [2]. On the other hand, the D6S273-138 allele showed a primary association with RA susceptibility [3]. Methods: We have selected 2 HLA-B7 and 5 HLA-B27 positive patients with a polyarticular course of JIA. Subjects were subtyped using PCR-SSP. Class III region microsatellite D6S273 alleles were analyzed by electrophoresis in an automated ALFexpress sequencer. Results: Analysis of D6S273 microsatellites showed that the most frequent alleles at D6S273 locus were D6S273-132 allele found in 4/5 HLA-B27 positive subjects. Both HLA-B7 patients had the D6S273-130 allele. One HLA-B27 positive patient had the D6S273-128 allele. Conclusions: Our preliminary data suggest that HLA-B27/B7 positive patients, diagnosed with polyarticular JIA had D6S273 microsatellites alleles different from D6S273-134, found previously in juvenile spondyloarthritis patients. Further analysis of additional polyarticular JIA patients, linkage disequilibria between these loci and HLA-B27/B7, as well as TNF-α microsatellites is currently underway. If confirmed in a larger patient population, these findings could present new challenges for the ILAR classification of JIA. References: Berntson, L., et al., HLA-B27 predicts a more extended disease with increasing age at onset in boys with juvenile idiopathic arthritis. The Journal of rheumatology, 2008; 35(10): p. 2055-61. Harjacek, M., et al., HLA-B*27/HLA-B*07 in combination with D6S273-134 allele is associated with increased susceptibility to juvenile spondyloarthropathies. Clin Exp Rheumatol, 2008; 26(3): p. 498-504. Singal, D.P., et al., D6S273 microsatellite polymorphism and susceptibility to rheumatoid arthritis. Tissue Antigens, 1998; 52(4): p. 353-8. Disclosure of Interest: None Declared